LRRK2 Kinase Inhibitor PF-06447475 Protects Drosophila melanogaster against Paraquat-Induced Locomotor Impairment, Life Span Reduction, and Oxidative Stress (2024)
ABSTRACT: Parkinson’s disease (PD) is a complex multifactorial progressive neurodegenerative disease characterized by locomotor alteration due to the specific deterioration of dopaminergic (DAergic) neurons in the substantia nigra pars compacta (SNpc). Mounting evidence shows that human LRRK2 (hLRRK2) kinase activity is involved in oxidative stress (OS)-induced neurodegeneration, suggesting LRRK2 inhibition as a potential therapeutic target. We report that the hLRRK2 inhibitor PF-06447475 (PF-475) prolonged lifespan, increased locomotor activity, maintained DAergic neuronal integrity, and reduced lipid peroxidation (LPO) in female Drosophila melanogaster flies chronically exposed to paraquat (PQ), a redox cycling compound, compared to flies treated with vehicle only. Since LRRK2 is an evolutionary conserved kinase, the present findings reinforce the idea that either reduction or inhibition of the LRRK2 kinase might decrease OS and locomotor alterations associated with PD. Our observations highlight the importance of uncovering the function of the hLRRK2 orthologue dLrrk2 in D. melanogaster as an excellent model for pharmacological screenings.